2021
DOI: 10.1093/biolre/ioaa233
|View full text |Cite
|
Sign up to set email alerts
|

A transgenic DND1GFP fusion allele reports in vivo expression and RNA-binding targets in undifferentiated mouse germ cells

Abstract: In vertebrates, the RNA binding protein (RBP) Dead End 1 (DND1) is essential for primordial germ cell (PGC) survival and maintenance of cell identity. In multiple species, Dnd1 loss or mutation leads to severe PGC loss soon after specification or, in some species, germ cell transformation to somatic lineages. Our investigations into the role of DND1 in PGC specification and differentiation have been limited by the absence of an available antibody. To address this problem, we used CRISPR/Cas9 gene editing to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 72 publications
2
14
0
Order By: Relevance
“…We previously used CRISPR/Cas9 to target the endogenous allele of Dnd1 and insert eGfp fused in frame to the 5' end of the Dnd1 gene (Dnd1 GFP ). This allele revealed heterogeneity in male germ cells (MGCs) during stages preceding mitotic arrest (E11.5-E14.5) [27], consistent with results from other labs [28][29][30]. We used DND1-GFP to isolate MGCs at later fetal stages.…”
Section: During Late Gestation Subpopulations Of Mgcs Express High Or...supporting
confidence: 81%
See 1 more Smart Citation
“…We previously used CRISPR/Cas9 to target the endogenous allele of Dnd1 and insert eGfp fused in frame to the 5' end of the Dnd1 gene (Dnd1 GFP ). This allele revealed heterogeneity in male germ cells (MGCs) during stages preceding mitotic arrest (E11.5-E14.5) [27], consistent with results from other labs [28][29][30]. We used DND1-GFP to isolate MGCs at later fetal stages.…”
Section: During Late Gestation Subpopulations Of Mgcs Express High Or...supporting
confidence: 81%
“…To solve this problem, we used CRISPR/Cas9 editing to establish a knock-in mouse line expressing a Dnd1 GFP fusion allele from the endogenous locus. In both male and female fetal development, levels of DND1 GFP expression varied among germ cells [27], consistent with heterogeneity in the germ cell population reported by multiple groups [28][29][30]. At E14.5, E16.5, and E18.5 we detected DND1 GFP -hi (DND1-GFP-hi) and DND1 GFPlo (DND1-GFP-lo) expressing populations.…”
Section: Introductionsupporting
confidence: 86%
“…As good antibodies for co-immunoprecipitation experiments for DND1 are still unavailable, these alleles allow pull down of DND1 binding partners with FLAG or myc antibodies. Furthermore, the newly reported transgenic mouse line carrying a Dnd1GFP fusion allele enables in vivo imaging of the DND1 protein and easy sorting of DND1 expressing cells [60].…”
Section: Genetically Engineered Mouse Alleles Of Dnd1mentioning
confidence: 99%
“…Dead end1 (DND1) is an RNA-binding protein implicated in germline development in mice. The expression of DND1 begins speci cally in PGCs immediately after PGC development, continues during the migration and colonisation of the embryonic testes, and becomes restricted to spermatogonia in adult testes after birth, whereas its expression gradually decreases after colonisation of the embryonic ovary, as embryonic development progresses, and disappears during oogenesis 16,17 . We have previously shown that DND1 directly interacts with another RNA-binding protein, NANOS2, in PGCs colonising the embryonic testes and suppresses the expression of target genes by recruiting the CCR4-NOT deadenylase complex to their mRNAs through NANOS2 for degradation 16 .…”
Section: Introductionmentioning
confidence: 99%